Csanád vármegye képviselete az 1811/12. évi országgyűlésen - Deák Ádám; Móra Kárpát-medencei Interdiszciplináris Szakkollégiumi Konferencia (6.) (2022) (Szeged) (Szegedi Tudományegyetem Móra Ferenc Szakkollégiuma Szeged, 2023)
The last years of the 18th century and the first decade and a half of the 19th century were dominated by the war against the French in the Habsburg Empire (the Austrian Empire was founded in 1806), which had a great influence on Hungarian domestic politics. The Diets (1796, 1802, 1805, 1807, 1808, 1811/12) were mostly about offering taxes and soldiers, and there were no real attempts at reform. The Estates constantly asked for the work of the nine regular committees sent out under Article 67 of 1791 to be discussed and the grievances remedied, but the Emperor did not contribute. As a result of the protracted wars against the French, the Habsburg Empire was plunged into a financial crisis as paper money became increasingly worthless. In 1810, there were already 1,060 million silver forints worth of paper money in circulation, and gold and silver coins (the conventional forint) were increasingly leaking out of the Habsburg Empire. In 1810, the Empire had a total income of 120 million forints and an expenditure of 1500 million forints. The government therefore resorted to devaluation, following a proposal by the Minister of Finance, Josef Wallis, who issued a royal decree on 20 February 1811 reducing the value of paper money to 1/5 and introducing the new banknote (Einlösscheine). The Diet of 1811/12 was also convened by the Emperor to discuss the financial situation. Antal Muslay and János Marczibányi represented Csanád county at this Diet. The parliamentary deliberations were mostly about discussing the financial system, but the deliberations were unsuccessful because both the king and the Hungarian orders insisted on their rights and privileges.
Keywords: Bölcsészettudományok; Történettudomány és régészet